Life cycle trends of electronic materials, processes and components. (August 2019) - Huang, Chien-Ming; Romero, Jose A.; Osterman, Michael; Das, Diganta; Pecht, Michael
Abstract: Most electronic products experience several stages in their life-cycle, including introduction, growth, maturity, decline, phase-out, and obsolescence. With the accelerated growth of the electronics industry, new materials, processes and components are being introduced at an increasing speed which adds to the complexity of the life cycle stages of electronic products. This paper presents the life cycle process and provides three examples to demonstrate how electronics materials, processes and components have life cycle changes. The paper then discusses the problems induced by rapid changes, including the need for re-qualification. Then methods to address the problems are presented, including lifetime buys, acquisition from the aftermarkets, uprating commercial components, and products re-design.